2022
DOI: 10.1039/d2md00216g
|View full text |Cite
|
Sign up to set email alerts
|

Advanced approaches of developing targeted covalent drugs

Abstract: This review highlights developing strategies of covalent drug discovery and successful applications to address challenges of designing effective covalent drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…The Goldscore suggested the possibility of carbonyl replacement to covalently bind to Cys145. The mechanism for the reaction of this carbonyl as an aldehyde group covalently bound with cysteine residue was previously described 43 , 44 . Their interactions to the amino acids in the binding pocket were also similar to the interactions found with PF-07321332.…”
Section: Resultsmentioning
confidence: 99%
“…The Goldscore suggested the possibility of carbonyl replacement to covalently bind to Cys145. The mechanism for the reaction of this carbonyl as an aldehyde group covalently bound with cysteine residue was previously described 43 , 44 . Their interactions to the amino acids in the binding pocket were also similar to the interactions found with PF-07321332.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the intrinsic reactivity of the 2-chloroacetamide electrophilic warhead in compound 6 , there are concerns about the risk of nonspecific covalent binding. In order to identify a safer covalent ZAP-70 inhibitor for in vivo use, we have replaced the 2-chloroacetamide in 6 with an acrylamide ( 7 ), which is commonly used as a mildly reactive warhead in approved covalent kinase drugs . We then evaluated these compounds for their chemical reactivity toward thiol using the glutathione (GSH) incubation assay, which included the covalent kinase drug afatinib as a control. , This result revealed that compound 7 exhibited higher stability when incubated with GSH, with a half-life of 254 min, compared to 6 ( t 1/2 = 54 min) and afatinib ( t 1/2 = 66 min), suggesting that compound 7 may have reduced chemical reactivity toward nonspecific targets (Supporting information, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the development of targeted covalent inhibitors has gained popularity worldwide. These inhibitors involve specific groups known as electrophilic warheads, which form irreversible bonds with nucleophilic amino acid residues in biological targets, such as proteins [ 283 ].…”
Section: Role Of Electrophilic Compounds In Diseasesmentioning
confidence: 99%